SISTEM INFORMASI PELANGGARAN SISWA BERBASIS WEB MENGGUNAKAN PHP NATIVE DI SMA KARTIKA 1-2 MEDAN - Siregar, Yafi Bayu Ahmad (Universitas Lampung, 2025)
The rapid development of information technology can be utilized to provide security and conciseness in a system. SMA Kartika 1-2 Medan is a school located in Medan, North Sumatra, still has a violation recording system that is stored manually in archives and notebooks. The purpose of this study is to build an information system and implement it to provide ease of recapitulation of student violations and also ensure the security of violation data at SMA Kartika 1-2 Medan. The initial testing applied to this system is black box testing, the results obtained are based on input and output. The research methodology includes the stages of needs analysis to the operational stage. The data collection process is carried out by observation, interviews, literature studies, and questionnaire. The system design uses UML diagrams, the programming languages ​​used are PHP, CSS and HTML, with a MySQL database manager. The final test is carried out using the System Usability Scale (SUS) method, the usability testing process is carried out by filling out a questionnaire by 5 respondents. The final usability score obtained is 70.5 with the category